‘MOTIDUPAPA' STRATEGI PEWARISAN TRADISI TUJA'I KEPADA GENERASI MUDA PADA MASYARAKAT GORONTALO - Laya, Rachmi (Jurnal Bahasa, Sastra, dan Budaya, 2024)
One of the oral literatures which is still used in Gorontalo custom event is Tuja'i Molo'opu. Oral literature is uttered at the ceremonial of official's reception in Gorontalo. As other traditions are changing, Tuja'i Molo'opu also along with the changes of the society. Therefore, it needs to be held as the Foundation for preservation of the study of oral literature Tuja'i Molo'opu. Thus, the ceremony Tuja'i Molo'opu this is not the complement of Molo'opu ceremony, but contain a moral, and ethical, and history of his supporters. The theory used in this research is the theory of orality Albert Bates Lord and Ruth Finnegan. To apply this theory is used Ethnographic aproach to explore data on composition and transmission, as the cultural aspects of the community of Gorontalo. Aspects of orality in this tuja'i Molo'opu covering composition. Composition is composing of oral literature, starting from: (1) the composition of the characters, (2) development techniques, (3) and repetition of the scene. In addition, transmission or starting inheritance from: (1) the transmission of natural processes, (2) a transmission process through training, (3) studing of acting, and (3) learning to talk.